Effects of slope instability on pockmark deformation on the continental slope in the southern South China Sea - Liu, Zhihao; Wu, Ziyin; Liu, Yang; Shang, Jihong; Zhou, Jieqiong; Zhang, Jialing (Frontiers in Marine Science, 2025)
Pockmark development and slope instability are key geological processes shaping the continental slope. In this study, high-resolution multibeam data, subbottom profiles, and a reprocessed two-dimensional seismic profile were used to identify and analyze the complex geomorphic features of landslides and pockmarks in the southern South China Sea. We analyzed the morphology of a landslide and 340 surrounding pockmarks, which are distributed on both sides of the landslide and exhibit a stepped pattern. Different from the pockmark deformation only along the slope, pockmarks in the study area exhibited deformation cross the slope. Based on the feature and distribution of pockmarks relative to the landslide, it is inferred that the development of the pockmarks triggers the landslide. Within the same depth interval, gravity and shear forces acting on the pockmarks intensify progressively from the center toward the flanks. In addition, tensile fracturing of the pockmarks significantly influences cross-slope deformation. On this basis, we established a three-stage model of pockmark evolution.